UMP hosts HEI 2022 Womens 7s Football Carnival - Siti Nur Azwin, Zulkapri (2022)
KUANTAN, 23 October 2022 – The HEI 2022 Women’s 7s Football Carnival organised by the Ministry of Higher Education (MoHE) saw Universiti Malaysia Pahang (UMP) as the host for the tournament which took place at UMP Sports Complex football field, Gambang Campus recently.